1994
DOI: 10.1029/94wr01458
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of surfactant‐enhanced aquifer remediation

Abstract: Surfactant‐enhanced aquifer remediation (SEAR) is currently under active investigation as one of the most promising alternatives to conventional pump‐and‐treat remediation for aquifers contaminated by dense nonaqueous phase organic liquids. An existing three‐dimensional finite‐difference enhanced oil recovery simulator is adapted to model the SEAR process. This simulator incorporates the complex chemistry and multiphase transport behavior of surfactant/water/organic mixtures in permeable media. Model governing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(48 citation statements)
references
References 28 publications
0
48
0
Order By: Relevance
“…Based on the estimated spatial variability of permeability and capillary parameters in the Borden aquifer, Kueper and Frind (1991) investigated the effect of local-scale heterogeneity on multiphase flow under different flow conditions. The transport of dense nonaqueous phase liquids (DNAPLs) and remediation in heterogeneous systems representing the Borden aquifer were also investigated by a number of researchers (e.g., Brown et al, 1994;Kueper and Gerhard, 1995;Mayer and Miller, 1996;Unger et al, 1998;Frind et al, 1999;Dekker and Abriola, 2000a,b). Jacobs (1999) derived the field-scale effective properties of multiphase flow in these two aquifers using spectral-perturbation analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the estimated spatial variability of permeability and capillary parameters in the Borden aquifer, Kueper and Frind (1991) investigated the effect of local-scale heterogeneity on multiphase flow under different flow conditions. The transport of dense nonaqueous phase liquids (DNAPLs) and remediation in heterogeneous systems representing the Borden aquifer were also investigated by a number of researchers (e.g., Brown et al, 1994;Kueper and Gerhard, 1995;Mayer and Miller, 1996;Unger et al, 1998;Frind et al, 1999;Dekker and Abriola, 2000a,b). Jacobs (1999) derived the field-scale effective properties of multiphase flow in these two aquifers using spectral-perturbation analysis.…”
Section: Introductionmentioning
confidence: 99%
“…4 indicates that ka is increased with increasing n-pentanol concentration and is essentially independent of the oil type. c) Incorporation of 80 into the function of ymin In our previous study 5, we have found an empirical correlation between 1mm and S* of the optimum surfactant formulations at 00=0.2 as follows Ymin KS (S*-b) (8) where, KS is the slope of the straight line; b is the abscissa of the intersection between this line and horizontal axis. b value represents the optimal salinity at which the system becomes one-phase microemulsion (ymu=0).…”
Section: Resultsmentioning
confidence: 99%
“…From the desired value of IFF, the S* required to bring the system to the optimum state, can be computed by Eq. (8). Eq.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…surfactant, co-solvent, or air sparging) remediation technologies. Most advanced simulators are based upon an adaptation of enhanced oil recovery models (Brown et al 1994;, and are predicated on assumptions of local thermodynamic equilibrium between phases. Some data from laboratory experiments of surfactant-enhanced solubilization and soil vapor extraction, however, indicate that local interphase mass transfer rates can severely limit DNAPL recovery (e.g.…”
mentioning
confidence: 99%